A system dynamics analysis of agricultural practices and food security in Nigeria - Chinemelum Amarachukwu Eneh; Onyenekenwa Cyprian Eneh (Journal of Health, Population and Nutrition)
Abstract Food insecurity in Nigeria has persisted for decades, resisting various agricultural policies and programmes since the 1970s. This study investigates the impacts of traditional agriculture (TA), sustainable agriculture (SA), and industrial agriculture (IA) on food security in Nigeria from 2000 to 2022, using a system dynamics modelling approach supported by optimization and linear programming techniques. The model also accounts for climate change and land resource dynamics, integrating data from Nigeria and nine comparable countries to enhance robustness. Results show that while crop yield increased over time, food security fluctuated due to factors including land degradation and uneven food distribution. The findings highlight that improving agricultural productivity alone is insufficient; sustainable practices, climate adaptation, and improved distribution systems are essential for long-term food security in Nigeria.